TAMIZAJE DE UNA LIBRERÍA DE cDNA DE TRYPANOSOMA CRUZ/ CON UNA MEZCLA DE SUEROS CHAGÁSICOS CRÓNICOS - Pavía, Paula; Laboratorio de Parasitología Molecular Departamento de Microbiología Facultad de Ciencias Pontificia Universidad Javeriana, Bogotá (2013)
In this work was carried out a screening of cDNA library of Trypanosoma cruzi with a pool of chronic chagasicsera. The PI, P2, P3, and P4 clones were seiected based on its higher reactivity. Two ofthese clones were identical(P2 and P4 ). P 1 codes for the carboxy-terminal of the EF-Hand 5 variant 1 pro te in of T. cmzi. P2 and P3 code forthe carboxy-terminal of probably new parasite proteins that Jack homology with previously reported proteins.M oreo ver, it is probably that P3 encodes a membrane protein of the parasite. The presence of the PI, P2, and P3products in the trypomastigote stage of the parasite, and the immune recognition of them by chronic chagasic serabut not by healthy controls; make these proteins candidates for markers associated with chronic phase of Chagasdisease.